If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-76=4(3b-1)
We move all terms to the left:
-76-(4(3b-1))=0
We calculate terms in parentheses: -(4(3b-1)), so:We get rid of parentheses
4(3b-1)
We multiply parentheses
12b-4
Back to the equation:
-(12b-4)
-12b+4-76=0
We add all the numbers together, and all the variables
-12b-72=0
We move all terms containing b to the left, all other terms to the right
-12b=72
b=72/-12
b=-6
| 6t+4t-6t+2t+t=14 | | (5x+6)+64=180 | | 59+3x=90 | | 9x-7x-x+4x=15 | | 1/8b=64 | | 10=q/6 | | -84=-4(1-4x) | | 11n-n-6n=20 | | -84=-4(1-4x | | 13+2x-9=5x-4-(-3x) | | 8x+4x-14=22 | | 3x−2=18+x | | 1+x-5x=9 | | 6n–5=19 | | 29(x+9)=24 | | −6=−8+p/11 | | 6(3p-2)=-120 | | 2(2w+5)-6w=-3w+18-3w+24 | | 7x-13=5x+4 | | 7y+10=31 | | 11=8(m-3)+4m-1 | | x–6/2=4x/7 | | -70=-2(5v+5) | | -3x-1-5x=-9 | | 5=z−251 | | 3(5g+2)/2=63 | | 3y-9=54 | | 98=s+24 | | -70=-2(5v+5 | | −7k=49 | | 7=j/3 | | -2(3y-8)=7(-2y-8) |